Understanding patient preferences for emergency care for lower triage acuity presentations during GP hours: a qualitative study in Australia - Viola Korczak; Kenneth Yakubu; Blake Angell; Paul Middleton; Michael Dinh; Thomas Lung; Stephen Jan (BMC, 2022)
Abstract Background Low acuity presentations to Australian emergency departments drive long wait times, higher costs and may be better treated in primary care settings. This study sought to understand factors leading these patients to present to emergency departments. Methods Semi-structured interviews were carried out with patients at two tertiary emergency departments in Sydney during general practitioner opening hours. Nvivo was used to code the interviews and a thematic analysis was carried out to capture the main themes from the interviews. Results Forty-four interviews were included in the analysis across the two sites. They represented a diverse population in terms of ethnicity, education and socioeconomic background. Patient preferences for emergency care were organised into four main themes: (i) patients were referred (either by another health service, work, friend, or family), (ii) emergency department factors (convenience of investigations and severity of symptoms requiring emergency care), (iii) GP factors (does not have a GP, cannot find an appointment with a GP or has previously had a negative experience with a GP) and (iv) personal factors such as their connection to the hospital. Conclusion Multiple factors led patients to seek ED care for low acuity presentations during GP hours. Some of these factors could be addressed to meet patient needs in the community, however this is currently not the case. Addressing these factors to improve access to GP clinics and the availability of services outside the hospital setting could reduce ED presentations and likely improve patient experience.